Full Esteem Ahead? Mindset-Oriented Business Training in Ethiopia - Alibhai, Salman (World Bank, Washington, DC, 2019)
Is there a mindset gap holding women back in business? Can entrepreneurship training instill a set of attitudes, behaviors, and strategies that are thought to underpin success in business such as motivation, perseverance, and self-confidence? This study conducted two randomized controlled trials to evaluate the effect of mindset-oriented business trainings on the performance of women-owned micro and small enterprises in Ethiopia. The trainings were underpinned by psychology with a mission to foster self-esteem and entrepreneurial spirit. Despite a similar approach, however, the quality of delivery seemed to matter as impacts of the trainings on business performance were mixed. A key channel for an impact on profits is if the training can actually effectuate the mindset change, with only one training transferring higher levels of entrepreneurial self-efficacy, personal initiative, and entrepreneurial locus of control to the women, relative to a control group. The study finds suggestive evidence that psychological skills and mindset are better inspired by a trainer who previously owned a business themselves and therefore may have a better understanding of the entrepreneurs' specific challenges. The study concludes that psychological skills are important for women's business success, and these skills can indeed be transferred using training, assuming a shared identity match between trainer and student. Service delivery appears to be critical for inculcating these important skills.